High-throughput mutation analysis in patients with a nephronophthisis-associated ciliopathy applying multiplexed barcoded array-based PCR amplification and next-generation sequencing. Issue 12 (27th November 2012) - Halbritter, Jan; Diaz, Katrina; Chaki, Moumita; Porath, Jonathan D; Tarrier, Brendan; Fu, Clementine; Innis, Jamie L; Allen, Susan J; Lyons, Robert H; Stefanidis, Constantinos J; Omran, Heymut; Soliman, Neveen A; et al.
Abstract : Objective: To identify disease-causing mutations within coding regions of 11 known NPHP genes ( NPHP1-NPHP11 ) in a cohort of 192 patients diagnosed with a nephronophthisis-associated ciliopathy, at low cost. Methods: Mutation analysis was carried out using PCR-based 48.48 Access Array microfluidic technology (Fluidigm) with consecutive next-generation sequencing. We applied a 10-fold primer multiplexing approach allowing PCR-based amplification of 475 amplicons (251 exons) for 48 DNA samples simultaneously. After four rounds of amplification followed by indexing all of 192 patient-derived products with different barcodes in a subsequent PCR, 2×100 paired-end sequencing was performed on one lane of a HiSeq2000 instrument (Illumina). Bioinformatics analysis was performed using 'CLC Genomics Workbench' software. Potential mutations were confirmed by Sanger sequencing and shown to segregate. Results: Bioinformatics analysis revealed sufficient coverage of 30×for 168/192 (87.5%) DNA samples (median 449×) and of 234 out of 251 targeted coding exons (sensitivity: 93.2%). For proof-of-principle, we analysed 20 known mutations and identified 18 of them in the correct zygosity state (90%). Likewise, we identified pathogenic mutations in 34/192 patients (18%) and discovered 23 novel mutations in the genes NPHP3 (7), NPHP4 (3), IQCB1 (4), CEP290 (7), RPGRIP1L (1), and TMEM67 (1). Additionally, we found 40 different single heterozygous missense variants of unknown significance. Conclusions: We conclude that the combined approach of array-based multiplexed PCR-amplification on a Fluidigm Access Array platform followed by next-generation sequencing is highly cost-efficient and strongly facilitates diagnostic mutation analysis in broadly heterogeneous Mendelian disorders.